Draft Annual Plan 2009-2010 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2009)
Arunachal Pradesh with a population of only 10.97 lakh as per 2001 Census inhabiting over an area of 83,743 sq. km., largest amongst NE States, has a very low density of 13 people per sq. km. About two third of its population belongs to Scheduled Tribe (64.22%) from 26 major tribes and more than 100 sub-tribes. the State is known for its ethnic, linguistic, cultural, religious and physiographical diversity. the State possesses a heterogeneous demographic character with distinct variations from each other in regard to dialects, culture, social customs and ethos.
Government of Arunachal Pradesh, Department of Planning